Generational career shifts : how matures, boomers, gen Xers, and millennials view work - Ng, Eddy S.; Lyons, Sean T.; Schweitzer, Linda (Emerald points., 2018)
"Organizations and employers are currently managing an inter-generational workforce, and the most prudent of these are seeking to enhance the careers of new entrants. HRM, careers, and work researchers have begun to explore career-related differences among the four generations of workers currently in employment, but to date there has been very little in the way of full-length comparative studies. In Generational Career Shifts: How Veterans, Boomers, Xers, and Millennials View Work, Eddy S. Ng, Sean T. Lyons, and Linda Schweitzer develop a timely, wide-ranging examination of inter-generational differences in work priorities, career attitudes, career experiences, and career outcomes. Offering a comprehensive overview of existing research, and drawing upon the authors' own largescale study of students and knowledge workers, this book documents how careers have fundamentally shifted over the past five decades. Along the way, it offers crucial insights into what these shifts mean for employers and their management strategies. Generational Career Shifts is essential reading for career researchers, generational researchers, practitioners within executive education, as well as for career counsellors, human resource departments, corporate libraries, and people managers."--